ASSESSMENT OF THE AGROECOLOGICAL CONDITION OF THE DRІED LANDS OF THE MANEVICH DISTRICT OF THE VOLYN REGION - Bondarchuk, S.; Bondarchuk, L.; Merlenko, I.; Kovalchuk, N. (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The research is devoted to agrochemical and agroecological assessment of the current state of the drained soils of the Manevychi district of Volyn region. The results obtained will allow a more rational approach to the directions of their further use.